Reputation: 1019
I have two lists which I want to group on the basis of the first element of the lists.
list1 = [['1','abc','zef'],['2','qwerty','opo'],['3','lol','pop']]
list2 = [['1','rofl','pole'],['2','sole','pop'],['3','lmao','wtf']]
Here the first elements in the list inside the list are '1' , '2' and '3'.
I want my final list to be like :-
Final_List = [['1', 'abc', 'zef', 'rofl', 'pole'], ['3', 'lol', 'pop', 'lmao', 'wtf'], ['2', 'qwerty', 'opo', 'sole', 'pop']]
I have tried this using below code.
#!/usr/bin/python
list1 = [['1','abc','zef'],['2','qwerty','opo'],['3','lol','pop']]
list2 = [['1','rofl','pole'],['2','sole','pop'],['3','lmao','wtf']]
d = {}
for i in list1:
d[i[0]] = i[1:]
for i in list2:
d[i[0]].extend(i[1:])
Final_List = []
for key, value in d.iteritems():
value.insert(0,key)
Final_List.append(value)
This code works but i was wondering if there was an easy and cleaner way to do it
Any help?
Upvotes: 2
Views: 2407
Reputation: 3059
list1 = [['1','abc','zef'],['2','qwerty','opo'],['3','lol','pop']]
list2 = [['1','rofl','pole'],['2','sole','pop'],['3','lmao','wtf']]
Final_List = []
for i in range(0, len(list1)):
Final_List.append(list1[i] + list2[i])
del Final_List[i][3]
print Final_List
Output
[['1', 'abc', 'zef', 'rofl', 'pole'], ['2', 'qwerty', 'opo', 'sole', 'pop'], ['3', 'lol', 'pop', 'lmao', 'wtf']]
Upvotes: 0
Reputation: 23753
A bit of functional style:
import operator, itertools
from pprint import pprint
one = [['1','abc','zef'],['2','qwerty','opo'],['3','lol','pop']]
two = [['1','rofl','pole'],['2','sole','pop'],['3','lmao','wtf']]
A few helpers:
zero = operator.itemgetter(0)
all_but_the_first = operator.itemgetter(slice(1, None))
data = (one, two)
def foo(group):
# group is (key, iterator) from itertools.groupby
key = group[0]
lists = group[1]
result = list(key)
for item in lists:
result.extend(all_but_the_first(item))
return result
Function to process the daa
def process(data, func = foo):
# concatenate all the sublists
new = itertools.chain(*data)
# group by item zero
three = sorted(new, key = zero)
groups = itertools.groupby(three, zero)
# iterator that builds the new lists
return itertools.imap(foo, groups)
Usage
>>> pprint(list(process(data)))
[['1', 'abc', 'zef', 'rofl', 'pole'],
['2', 'qwerty', 'opo', 'sole', 'pop'],
['3', 'lol', 'pop', 'lmao', 'wtf']]
>>>
>>> for thing in process(data):
print thing
['1', 'abc', 'zef', 'rofl', 'pole']
['2', 'qwerty', 'opo', 'sole', 'pop']
['3', 'lol', 'pop', 'lmao', 'wtf']
>>>
Upvotes: 0
Reputation: 1
list3 = []
for i in xrange(0,max(len(list1[0]), len(list2[0]))):
list3.append(list(list1[i]))
list3[i].extend(x for x in list2[i] if x not in list3[i])
with a xrange, you can iterate only once through the list.
Upvotes: 0
Reputation: 9647
If item sequence in the lists inside of the Final_List
is not important then this can be used,
[list(set(sum(itm, []))) for itm in zip(list1, list2)]
Upvotes: 1
Reputation: 239473
I would have written like you have written with a little modification, like this
Prepare a dictionary with all the elements from the second position gathered corresponding to the first element.
d = {}
for items in (list1, list2):
for item in items:
d.setdefault(item[0], [item[0]]).extend(item[1:])
And then just get all the values from the dictionary (Thanks @jamylak) :-)
print(d.values())
Output
[['3', 'lol', 'pop', 'lmao', 'wtf'],
['1', 'abc', 'zef', 'rofl', 'pole'],
['2', 'qwerty', 'opo', 'sole', 'pop']]
Upvotes: 5
Reputation: 39397
Using default dict and list comprehensions you can shorten your code
from collections import defaultdict
list1 = [['1','abc','zef'],['2','qwerty','opo'],['3','lol','pop']]
list2 = [['1','rofl','pole'],['2','sole','pop'],['3','lmao','wtf']]
d = defaultdict(list)
for i in list1 + list2:
d[i[0]].extend(i[1:])
Final_List = [[key] + value for key, value in d.iteritems()]
print Final_List
Upvotes: 0
Reputation: 9323
Yes, with list comprehension and enumerate
list1 = [['1','abc','zef'],['2','qwerty','opo'],['3','lol','pop']]
list2 = [['1','rofl','pole'],['2','sole','pop'],['3','lmao','wtf']]
print [set(v + list2[k]) for k,v in enumerate(list1)]
[['1', 'abc', 'zef', 'rofl', 'pole'], ['2', 'qwerty', 'opo', 'sole', 'pop'], ['3', 'lol', 'pop', 'lmao', 'wtf']]
EDIT
With index relation
list1 = [['1','abc','zef'],['2','qwerty','opo'],['3','lol','pop']]
list2 = [['1','rofl','pole'],['3','lmao','wtf'],['2','sole','pop']]
d1 = {a[0]:a for a in list1}
d2 = {a[0]:a for a in list2}
print [set(v + d2[k]) for k, v in d1.items()]
Upvotes: 0
Reputation: 13804
Your code seems correct. Just modify the following portion:
Final_List = []
for key in d:
L = [key] + [x for x in d[key]]
Final_List.append(L)
Upvotes: 0